痰火에 대한 形象醫學的 고찰 - 김종원(Jong Won Kim); 전수형(Soo Hyung Jun); 지규용(Gyu Yong Ji); 김경철(Kyung Chul Kim); 이인선(In Sun Lee); 이태식(Tae Sik Lee); 김규곤(Kyu Kon Kim); 이용태(Yong Tae Lee) (동의생리병리학회지, 2009)
Many of our contemporaries suffer from the symptoms of phlegm-fire, which is caused by stress, processed food, heavy diet, and unseasonal fruits and vegetables. With consultations from ‘EuihakIpmoon', ‘DongeuiBogham', and ‘Ji-San's clinical lectures' this research, which is mainly focused on phlegm-fire, concluded as following. Phlegm-fire is caused by congestion of seven emotions, congestion of qi, complication of phlegm on fire, depletion of body fluids after long periods of disease, heavy diet, or congenital unbalance of yin-yang and qi-hyul. Concentration of phlegm-fire on the head causes headache, dizziness, frontal headache, tinnitus, and auditory dysfunction. The patient usually complains breaking pain. Dhamhwabang of Yijin-tang, Chunghoonhwadham-tang, and Yijin-tang variation for right headache can be used. Concentration of phlegm-fire on the thorax causes insomnia, palpitation, and insanity. Samhoohndham-tang variation, Chungsimgondhanhwan can be used. Concentration of phlegm-fire on the gastric region causes reflux of gastric acid, eructation, vomiting, abdominal discomfort, dysmenorrhea, and fluor gentalis. Yijin-tang variation for abdominal discomfort, Yanghyulsamul-tang, Hwadhamchunghwa-tang can be used. Shin type or Gi type, female with prevalence of qi and tendency of fire, female with dark facial color, female with raised eye tails and large noses, female with pointed noses, and male or female with large noses and mouths are likely to possess phlegm-fire. Abdominal discomfort of male with thick eyebrow and headache of Gi type female is usually caused by phlegm-fire. KCI Citation Count: 2